Recognition of HSPB8 as a potential therapeutic target for prostate cancer - Fu, Xun; Wang, Yutao; Li, Hongjun (Frontiers in Genetics, 2025)
Prostate cancer poses a serious burden on men’s quality of life. Identifying novel biomarkers for therapeutic development and prognostic prediction has long been a focal point in prostate cancer research. HSP family is a group of molecular chaperones that exhibit close relationship with many cancer types. In this study we screened out HSPB8 as a potential biomarker using WGCNA. Then we analyzed its expression patterns, investigated its biological functions, and assessed its prognostic values with a combination of bioinformatic analyses and experimental validation. Our data demonstrated that HSPB8 exhibited lower expression levels in prostate cancer tissues than in normal prostatic tissues. As a tumor suppressor gene, lack of HSPB8 was associated with unfavorable survival outcomes among patients with prostate cancer. In terms of biological function, HSPB8 were predominantly enriched in muscle-related biological processes, such as muscle contraction and muscle cell differentiation. On the molecular and cellular levels, HSPB8 silencing induced cellular proliferation and enhanced invasive and migratory capacities of prostate cancer cell lines. Its tumor-suppressive function was likely mediated through inactivation of PI3K−AKT signaling. Overall, this study offers a new understanding into the pathogenesis of prostate cancer, proposing that targeting HSPB8 might be a promising area in prostate cancer treatment.